Pengaruh Budaya Kerja dan Jam Kerja Terhadap Kinerja Karyawan Pada Pt. Latexindo Toba Perkasa Binjai - Arief Rahmadsah Siregar; Patar Marbun; Yuni Syaputri (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
PT. Latexindo Toba Perkasa Binjai is a company engaged in the production of latex gloves. The purpose of this research is to test the influence of Work Culture and Working Hours on employee performance partially and simultaneously at PT. Latexindo Toba Perkasa Binjai. This research approach is based on a quantitative approach. The population and sample in this study were employees of PT. Latexindo Toba Perkasa Binjai which amounted to 103 employees. Data analysis using multiple linear regression and coefficient of determination. The results of the study show that partially, competency and supervision have a significant positive effect on the performance of employees at PT. Latexindo Toba Perkasa Binjai. Simultaneously, Work Culture and Working Hours have a significant positive effect on employee performance at PT. Latexindo Toba Perkasa Binjai. Employee performance is influenced simultaneously by Work Culture and Working Hours by 65.2% meaning that the ability of the performance variable (Y) can be explained by variations in the variable Work Culture (X1) and Working Hours (X2)of 65.2% the remaining 34.8% is explained by the other variables not examined in this study such as compensation, work environment, and so on.